Advances in understanding the regulation of pluripotency fate transition in embryonic stem cells - Jia, Yong kang; Yu, Yang; Guan, Li (Frontiers in Cell and Developmental Biology, 2024)
Embryonic stem cells (ESCs) sourced from the inner cell mass of blastocysts, are akin to this tissue in function but lack the capacity to form all extraembryonic structures. mESCs are transient cell populations that express high levels of transcripts characteristic of 2-cell (2C) embryos and are identified as “2-cell-like cells” (2CLCs). Previous studies have shown that 2CLCs can contribute to both embryonic and extraembryonic tissues upon reintroduction into early embryos. Approximately 1% of mESCs dynamically transition from pluripotent mESCs into 2CLCs. Nevertheless, the scarcity of mammalian embryos presents a significant challenge to the molecular characterization of totipotent cells. To date, Previous studies have explored various methods for reprogramming pluripotent cells into totipotent cells. While there is a good understanding of the molecular regulatory network maintaining ES pluripotency, the process by which pluripotent ESCs reprogram into totipotent cells and the associated molecular mechanisms of totipotent regulation remain poorly understood. This review synthesizes recent insights into the regulatory pathways of ESC reprogramming into 2CLC, exploring molecular mechanisms modulated by transcriptional regulators, small molecules, and epigenetic changes. The objective is to construct a theoretical framework for the field of researchers.